Assessment of fetal risk associated with exposure to cancer chemotherapy during pregnancy: a multicenter study - Peres,R.M. (2001)
The objective of the present study was to evaluate and quantify fetal risks involved in the administration of cancer chemotherapy during gestation, as well as to assess the long-term effects on the exposed children. In this retrospective, cohort study, we reviewed the records of women aged 15 to 45 years with a diagnosis of malignancy or benign tumors with malignant behavior at three reference services in the State of Rio Grande do Sul, Brazil, from 1990 to 1997. All patients with a diagnosis of pregnancy at any time during the course of the disease were selected, regardless of whether or not they received specific medication. Fetal outcomes of 14 pregnancies with chemotherapy exposure were compared to that of 15 control pregnancies in which these drugs were not used. Long-term follow-up of the exposed children was carried out. Fisher's exact test was used to compare the groups. Continuous variables were compared by the Wilcoxon-Mann-Whitney test. We found an increased rate of prematurity (6/8 vs 2/10; RR: 3.75; CI: 1.02-13.8; P = 0.03) in the exposed group. There was a trend to an increased fetal death rate (4/12 vs 0/10; P = 0.07) in the group exposed to chemotherapy. No malformations were detected in any child, which can be related to our small sample size as well as to the fact that most exposures occurred after the first trimester of pregnancy. Other larger, controlled studies are needed to establish the actual risk related to cancer chemotherapy during pregnancy.